Evaluation of compliance with standards for protection against the health effects of non-ionizing radiation from microwave ovens - Cruz Ornetta, Victor (2008)
The main objective of this study was to give a very simple approach to exposure levels from extremely low frequency fields (ELF) and radiofrequency (RF) electromagnetic fields from a sample of typical microwave ovens in Lima city, in arder to asses the compliance of emissions limits established by IEEE and the maximum exposure limits established as reference levels in the ICNIRP 's Guidelines. This work was carried out on a sample of 14 domestic microwaves ovens from different brands, installed in several office in INICTEL-UNI, in Lima city, in 2006. It consisted of a bibliographic research on biological and health efjects related to frequencies used in microwaves oven; a bibliographic research on emission and exposure limits; and measurements of ELF electric and magnetic fields at 60 Hz plus measurements of radiofrequency electric fields at 2. 4 GHz, evaluating them against international emission and exposure limits. In any case the measured values were in compliance with emission and exposure limits being coherent withfield values evaluated everywhere.